Simulation of micromechanical characteristics of coal seam grouting based on particle flow method - LIU Ming; XUE Bing; HU Guojian; CHEN Yongke (Meikuang Anquan, 2022)
Grouting method is one of the commonly used methods for soft roadway reinforcement. Through the discrete element simulation method, the grouting process of coal seam was studied, and the grouting effect under different coal strength and grouting pressure was explored, and the diffusion form of the slurry in the coal seam was obtained. The results show that: the coal seam grouting goes through the stage of “permeation-rapid splitting-slow splitting-stability”. The crack expansion in the grouting process is mainly caused by the tensile stress at the crack tip. Under the action of slurry pressure, the tensile stress concentration is formed at the crack tip, and the slurry splits the coal seam when the starting pressure is reached. Grouting pressure and coal strength have great influence on grouting effect, and the influence of grouting pressure on slurry diffusion radius decreases gradually. The smaller the compressive strength of coal is, the larger the grouting diffusion radius is, and the more fully developed the fracture is.